SMAC Mimetic BV6 Enables Sensitization of Resistant Tumor Cells but also Affects Cytokine-Induced Killer (CIK) Cells: A Potential Challenge for Combination Therapy - Rettinger, Eva; Glatthaar, Andreas; Abhari, Behnaz Ahangarian; Oelsner, Sarah; Pfirrmann, Verena; Huenecke, Sabine; Kuçi, Selim; Kreyenberg, Hermann; Willasch, Andre M.; Klingebiel, Thomas; Fulda, Simone; Bader, Peter (Frontiers in Pediatrics, 2014)
Allogeneic hematopoietic stem cell transplantation (HSCT) is an established treatment option for high-risk hematological malignancies, and may also be offered to patients with solid malignancies refractory to conventional therapies. In case of patients’ relapse, refractory tumor cells may then be targeted by cellular therapy-based combination strategies. Here, we investigated the potential of small molecule IAP inhibitor (SMAC mimetic) BV6 in increasing cytokine-induced killer (CIK) cell-mediated cytotoxicity against different tumor targets. Four hour pre-incubation with 2.5 μMol BV6 moderately enhanced CIK cell-mediated lysis of hematological (H9, THP-1, Tanoue) and solid malignancies (RH1, RH30, TE671). However, BV6 also increased apoptosis of non-malignant cells like peripheral blood mononuclear cells and most notably had an inhibitory effect on immune cells potentially limiting their cytotoxic potential. Hence, cytotoxicity increased in a dose dependent manner when BV6 was removed before CIK cells were added to tumor targets. However, cytotoxic potential was not further increasable by extending BV6 pre-incubation period of target cells from four to 12 hours. Molecular studies revealed that BV6 sensitization of target cells involved activation of caspases. Here we provide evidence that SMAC mimetic may sensitize targets cells for CIK cell-induced cell death. However, BV6 also increased apoptosis of non-malignant cells like CIK cells and peripheral mononuclear cells. These findings may therefore be important for cell- and small molecule IAP inhibitor- based combination therapies of resistant cancers after allogeneic HSCT.